Cytosine-Functionalized Macrocyclic Receptor for Nucleotides: Combining Three Recognition Motifs - Morozov, Boris; Oshchepkov, Aleksandr; Xu, Dan; Kataev, Evgeny (European Journal of Organic Chemistry, 2023)
Nucleoside monophosphates perform various essential functions and serve as second messengers in living systems. Despite the success of nucleotide-selective probes based on proteins, the creation of synthetic receptors for nucleoside monophosphates remains a challenging task. In this paper, we explore the design of synthetic receptors based on a combination of three recognition motifs. We show that each binding motif contributes to the formation of the host-guest complexes. The core macrocycle provides recognition of the phosphate residue of the nucleotide, while naphthalimide and the attached cytosine residue participate in the coordination of the nucleobase via π-π and hydrogen bonding interactions. The presence of cytosine in the receptor structure substantially increases the overall affinity of receptors for nucleotides. A considerable increase (100-fold) in binding affinities is observed for the tetranucleotide DNA sequences 5′-GGGG -3′ and 5′-CCCC-3′, as compared to the previously reported system without the attached cytosine.
CRIS-Team Scopus Importer:2023-12-15
Keywords: anion sensing; cyclic di-GMP; guanosine; naphthalimide; nucleotide recognition

Dye-functionalized phosphate-binding macrocycles: from nucleotide to G-quadruplex recognition and "turn-on" fluorescence sensing - Oshchepkov, Aleksandr; Reznichenko, Oksana; Xu, Dan; Morozov, Boris; Granzhan, Anton; Kataev, Evgeny (Chemical Communications, 2021)
A novel strategy to design "turn-on" fluorescent receptors for G-quadruplexes of DNA is presented, which relies on the connection of phosphate binding macrocycles (PBM) with naphthalimide dyes. A new PBM-dye family was synthesized and evaluated in terms of binding and detection of nucleotides and DNA G-quadruplexes of different topologies.
CRIS-Team WoS Importer:2021-10-08

Effects of Ring Functionalization in Anthracene-Based Cyclophanes on the Binding Properties Toward Nucleotides and DNA - Basaran, Ismet; Agafontsev, Aleksandr; Morozov, Boris; Oshchepkov, Alexander S.; Imhof, Petra; Kataev, Evgeny (Chemistry - A European Journal, 2024)
Supramolecular recognition of nucleobases and short sequences is an emerging research field focusing on possible applications to treat many diseases. Controlling the affinity and selectivity of synthetic receptors to target desired nucleotides or short sequences is a highly challenging task. Herein, we elucidate the effect of substituents in the phenyl ring of the anthracene-benzene azacyclophane on the recognition of nucleoside triphosphates (NTPs) and double-stranded DNA. We show that introducing phenyl rings increases the affinity for NTPs 10-fold and implements groove and intercalation binding modes with double-stranded DNA. NMR studies and molecular modeling calculations support the ability of cyclophanes to encapsulate nucleobases as part of nucleotides.
CRIS-Team Scopus Importer:2024-10-11
Keywords: Cyclophanes; Fluorescence sensing; Nucleotide; Recognition; π–π interaction

Fluorescent macrocycle-dye-anchor conjugates for sensing phospholipids in biomembranes - Oshchepkov, Alexander S.; Cruz Da Silva, Elisabete; Morozov, Boris; Aparin, Ilya O.; Kataev, Evgeny; Klymchenko, Andrey S. (Sensors and Actuators B-Chemical, 2023)
Negatively charged phospholipids can serve as biomarkers for a number of biological processes allowing detection of apoptosis in animal cells, drug-induced phospholipidosis as well as detection of bacteria. Selective detection of phospholipids thus represents an important but challenging goal. The development of fluorescent probes capable of selective recognition of specific phospholipids can be a promising solution to the problem. Along this line, we have developed the macrocycle-dye-anchor conjugates, in which the macrocycle recognizes the phosphate residue, hydrocarbon anchors ensure hydrophobic interaction with the membrane, and environment-sensitive fluorescent dye functions as a reporter unit. To the best of our knowledge, this is the first report of synthetic fluorescent probes for specific phospholipids using the macrocycle-dye-anchor concept. We have studied the effect of the structure of the anchor and the macrocycle on the resulting fluorescent response in the presence of two types of lipid vesicles: phosphatidylcholine as a model of healthy cells and phosphatidylcholine and phosphatidylserine (1:1), mimicking apoptotic cells. The properties of the obtained compounds were analyzed in various model media and in HeLa cells. The response of fluorescent probes has been found to be strongly dependent on the macrocycle structure, length of the anchor, nature of the buffer, and pH. The probes showed significant fluorescence enhancement in apoptotic cells, thus providing the proof of concept for the macrocycle-dye-anchor design.
CRIS-Team Scopus Importer:2023-05-19
Keywords: Anion recognition; Anion sensing; Fluorescence imaging; Membrane probes; Naphthalimide; Phospholipids

Helix-Like Receptors for Perrhenate Recognition Forming Hydrogen Bonds with All Four Oxygen Atoms - Morozov, Boris; Ravi, Anil; Oshchepkov, Aleksandr; Rueffer, Tobias; Lang, Heinrich; Kataev, Evgeny (Chemosensors, 2021)
Supramolecular recognition of perrhenate is a challenging task due to therelatively large size and low charge density of this anion. In this work, we design and synthesize a family of helix-like synthetic receptors that can bind perrhenate by forming hydrogen bonds with all four oxygen atoms of the anion. Among the investigated rigid helix-forming subunit derived from 1,1 '-ferrocenedicarboxylic acid, 1,3-phenylenediacetic acid and 2,2 '-(ethyne-1,2-diyl)dibenzoic acid, the latter one shows the best selectivity for perrhenate recognition. However, the receptor based on 1,1 '-ferrocenedicarboxylic acid demonstrates selectivity to bind chloride in a 1:2 fashion. The properties of the receptors are investigated in the acetonitrile solution by using NMR, UV-Vis, and in the solid state by single crystal X-ray analysis.
CRIS-Team WoS Importer:2021-06-04

Macrocyclic Conformational Switch Coupled with Pyridinium-Induced PET for Fluorescence Detection of Adenosine Triphosphate - Morozov, Boris; Gargiulo, Fabiano; Ghule, Swapnil; Lee, Dong Joon; Kim, Hwan Myung; Kataev, Evgeny (Journal of the American Chemical Society, 2024)
The binding of nucleotides is crucial for signal transduction as it induces conformational protein changes, leading to downstream cellular responses. Synthetic receptors that bind nucleotides and transduce the binding event into global conformational rearrangements are highly challenging to design, especially those that operate in an aqueous solution. Much work is focused on evaluating functionalized dyes to detect nucleotides, whereas coupling of a nucleotide-induced conformational switching to a sensing event has not been reported to date. We disclose synthetic receptors that undergo a global conformational rearrangement upon nucleotide binding. Integrating naphthalimide and the pyridinium ion into the structure enables stabilization of the folded conformation and efficient fluorescence quenching. The binding of a nucleotide rearranges the receptor conformation and alters the strong fluorescence enhancement. The methylpyridinium-containing receptor demonstrated high sensing selectivity for adenosine 5′-triphosphate (ATP) and a record 160-fold fluorescence enhancement. It can detect fluctuations of ATP in HeLa cells and possesses low cytotoxicity. The developed systems present an attractive approach for designing ATP-responsive artificial molecular switches that operate in water and integrate a strong fluorescence response.<br

Mesoporous supraparticles with a tailored solid-liquid-gas interface for visual indication of H2 gas and NH3 vapours - Zink, Andreas; Reichstein, Jakob; Ruhland, Nico; Stockinger, Nina; Morozov, Boris; Cuadrado Collados, Carlos; Thommes, Matthias; Kataev, Evgeny; Wintzheimer, Susanne; Mandel, Karl (Chemical Communications, 2024)
Dual-gasochromic supraparticles that undergo rapid eye-readable and gas-specific colour changes upon reaction with hydrogen or ammonia are reported. This functionality is achieved by tailoring the solid-liquid-gas interface within the mesoporous framework of supraparticles via spray-drying.
CRIS-Team Scopus Importer:2024-06-14

Supramolecular Recognition of Cytidine Phosphate in Nucleotides and RNA Sequences - Morozov, Boris; Oshchepkov, Aleksandr S.; Klemt, Insa; Agafontsev, Aleksandr; Krishna, Swathi; Hampel, Frank; Xu, Honggui; Mokhir, Andriy; Guldi, Dirk Michael; Kataev, Evgeny (JACS Au, 2022)
Supramolecular recognition of nucleotides would enable manipulating crucial biochemical pathways like transcription and translation directly and with high precision. Therefore, it offers great promise in medicinal applications, not least in treating cancer or viral infections. This work presents a universal supramolecular approach to target nucleoside phosphates in nucleotides and RNA. The artificial active site in new receptors simultaneously realizes several binding and sensing mechanisms: encapsulation of a nucleobase via dispersion and hydrogen bonding interactions, recognition of the phosphate residue, and a self-reporting feature─“turn-on” fluorescence. Key to the high selectivity is the conscious separation of phosphate- and nucleobase-binding sites by introducing specific spacers in the receptor structure. We have tuned the spacers to achieve high binding affinity and selectivity for cytidine 5′ triphosphate coupled to a record 60-fold fluorescence enhancement. The resulting structures are also the first functional models of poly(rC)-binding protein coordinating specifically to C-rich RNA oligomers, e.g., the 5′-AUCCC(C/U) sequence present in poliovirus type 1 and the human transcriptome. The receptors bind to RNA in human ovarian cells A2780, causing strong cytotoxicity at 800 nM. The performance, self-reporting property, and tunability of our approach open up a promising and unique avenue for sequence-specific RNA binding in cells by using low-molecular-weight artificial receptors.
CRIS-Team Scopus Importer:2023-03-07
Keywords: cytosine; encapsulation; fluorescence sensing; nucleotide recognition; synthetic receptors